Kandungan Protein Kasar dan Tanin Biji Asam yang Difermentasi dengan Rhyzopus Oligosporus - Theresia Nur Indah Koni; Agustinus Paga; Antonius Jehemat (Politeknik Pertanian Negeri Kupang, 2013)
This research was aimed to evaluate the effect of level of Rhyzopus oligosporus and fermentation time on crude protein and tannin of tamarind seed. This experiment was conducted in 2 treatment factors with 2 replication. The first factor was various level of Rhyzopus oligosporus e.i. 1,2,3 kg/kg, and the second factor was time of fermentation e.i. 1,2,3, days. The results showed that there was no significantly effects among treatments on crude protein, but significant effect (P<0.05) on tannin by level of Rhyzopus oligosporus treatment, and time of fermentation, even those there was no interaction between each treatment. Tannin content decreased in line with increasing level of Rhyzopus oligosporus and time of fermentation. In conclusion, the best treatment was 3 g/kg level of Rhyzopus oligosporus with 3 days fermentation length.Key words: Rhyzopus oligosphorus, Fermentation time, tamarind seed, crude protein, Tannin